«More» and «more» with Christ. Christology and Holiness in the Light of «Gaudete et exsultate» - Gil Canto, Salvador (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The Second Vatican Council presented, in chapter V of the dogmatic constitution Lumen gentium, the universal call to holiness for all members of the people of God. Pope Francis, in his apostolic exhortation Gaudete et exsultate, has reminded of the validity and necessity of welcoming that call anew to become saints in the ecclesial and cultural context of our time. This paper reflects upon the most outstanding elements of the exhortation, aiming at a better understanding of the deep significance of this call to holiness. It looks into the Christological dimension suggested by the document, as well as the relationship between the mystery of Christ and the vocation to holiness. The call to holiness is a primary theological topic, based on He who is «the Holy One of God» (John 6,69). The model of holiness we are called to shines in the personal encounter with Christ. The dynamics of holiness demands the call by and the encounter with Christ, so that the christian existence is shaped after the forma Christi. Just as there is no holiness without Christ, there will be no missionary announcement or evangelization without a holy Church.
Keywords: Christ; Christology; holiness; Church; pastoral; mission